Political Legal Overview Perspective: Evaluating Human Rights in the Philippines (Journal of Governance and Development (JGD), 2008)
This writing examines and analyzes human rights issues in the Philippines. The author’s approach is primarily an eclectic, by concentrating on the strengths and weaknesses of the human rights’ regime as practiced by the Government of the Republic of the Philippines (GRP). This paper is divided into five parts. The first part discusses the historical evolution of human rights. The second part describes human rights in the Philippines. The third part analyzes the fundamentals of human rights that include: respect for the integrity of the person; respect for civil liberties; respect for political rights, more specifically, the rights of the Filipino citizens in the Philippines to change their government. The fourth part discusses the Philippine government’s attitude regarding international and non-governmental investigations of alleged violations of human rights such as discrimination based on religion, tribe and social status. And the fifth part concludes the study. The data for this analysis came from primary and secondary sources, namely newspapers, internet, books, magazines, and journals. The study found out that the records of human rights in the Philippines are not encouraging and indeed, there are serious breaches of human rights in the country. Though, the Philippines is known for its democratic experiences since its independence in 1946, but such practices were marred by vote-buying, rigging, fraud and other forms of cheating. Worst was during the regime of Ferdinand E. Marcos and the current Gloria M. Arroyo’s administration. Political arrests of some opposition leaders were common and physical force was exerted against their opponents. Indeed, Arroyo’s regime made history when it imprisoned the former President of the Philippines, Joseph Estrada, for corruption case. As such many fear that other former presidents of the country might fall into the same fate as Estrada’s-including the current president (Gloria M. Arroyo) after her terms as president ends.